Organizational Commitment: The Mediator for Work Motivation and Organizational Climate Toward Organizational Citizenship Behavior (OCB) - Suliati, Ni Nyoman; Sapta, I Ketut Setia; Sujana, I Wayan; Widnyani, Anak Agung Dwi (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The aim of this research is to know and analyse the role of mediated organizational commitment in determining work motivation, and organizational climate toward Organizational Citizenship Behaviour (OCB) of the employee at PT. Banoli Motor Denpasar. Census method is used in this research, where all the staff in total 76 people regarded as the sample. The data collected were then analysed further using structural equation modelling (SEM Analysis) with PLS technique. The findings of this research are; that work motivation has a positive and significant correlation towards organizational commitment, organizational climate contributes positively and significantly toward organizational commitment, work motivation does not significantly correlate toward OCB, organizational climate and organizational commitment have a significant and positive correlation toward OCB. Organizational commitment is proven as a full mediation between work motivation and OCB, and a partial mediation among organizational climate and OCB. These findings mean that mediation of organizational commitment can be the determinant on the indirect effect of work motivation toward OCB, and organizational climate toward OCB at PT. Banoli Motor’s staff Denpasar. Keywords: work motivation, organizational climate, organizational commitment, OCB, SEM-PLS